Ekosistem Pendidikan Karakter Berbasis al-Qur’an: Integrasi Kurikulum, Pembelajaran, dan Budaya Madrasah - Tofan Rinaldi; Muhammad Alfi Syahrin (ARZUSIN, 2026)
Although Al-Qur’an-based Islamic education has a strategic role in shaping students’ religious character, its implementation in madrasahs is often not yet systematically integrated into the curriculum and school culture. This study aims to analyze the implementation and internalization of Qur’anic values in shaping the religious character of students at MI Al-Ukhuwah Sukoharjo. This study employed a descriptive qualitative approach involving the madrasah principal, teachers, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results showed that Qur’anic values were implemented integratively through curriculum design, cross-subject learning processes, and the religious culture of the madrasah. The internalization process took place through habituation and teacher role modeling, which contributed to the formation of students’ religious character, as reflected in consistency in worship, honesty, trustworthiness, discipline, and social responsibility. This study concludes that Al-Qur’an-based Islamic education is effective in shaping religious character when it is systematically integrated into the institutional, pedagogical, and cultural ecosystem of the madrasah. These findings contribute to strengthening the study of character education based on Qur’anic values and provide practical implications for madrasahs in designing the sustainable integration of curriculum, learning, and school culture.